2013
DOI: 10.1007/s11746-012-2195-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Rapeseed Oil Produced by Conditioning Seeds at Modest Temperatures

Abstract: Conditioning rapeseed can significantly increase the amount of bioactive compounds in the crude oil, but if the conditioning temperatures are too high, they can cause unwanted side effects such as darker color and sensory defects. Modest conditioning temperatures may be more suitable, but little is known about the effects on the quality and bioactive composition of the resulting oil. Oil was recovered from five rapeseed cultivars by cold pressing (CP) or by pressing seeds conditioned at 80 °C for 30 min (HP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 26 publications
6
77
1
Order By: Relevance
“…Wijesundera et al (2008) reported that conditioning rapeseed at the temperature of 165 °C resulted in a modest increase in γ-tocopherol concentration with a practically unchanged content of α-tocopherol. However, Kraljic´ et al (2013) found that a moderate rapeseed conditioning temperature (80 °C) increased the α-tocopherol content, but no significant difference in the amount of γ-tocopherol was observed. On the other hand, Prior et al (1991a) found that roasting rapeseed (B. napus cv.…”
Section: Effect Of Roasting Conditions On the Content Of Tocopherolsmentioning
confidence: 82%
“…Wijesundera et al (2008) reported that conditioning rapeseed at the temperature of 165 °C resulted in a modest increase in γ-tocopherol concentration with a practically unchanged content of α-tocopherol. However, Kraljic´ et al (2013) found that a moderate rapeseed conditioning temperature (80 °C) increased the α-tocopherol content, but no significant difference in the amount of γ-tocopherol was observed. On the other hand, Prior et al (1991a) found that roasting rapeseed (B. napus cv.…”
Section: Effect Of Roasting Conditions On the Content Of Tocopherolsmentioning
confidence: 82%
“…Unlike other phenolics, canolol, due to its molecular structure, shows better solubility in oil. As a result, canolol constitutes a dominant phenolic compound found in rapeseed oil (Kraljić et al, 2013;Shrestha and De Melnauer, 2014;Yang et al, 2014;Siger et al, 2015). The canolol concentration in rapeseed oil pressed from roasted seeds greatly depends on the applied heating temperature, duration of heating and moisture content of the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…In the control test (using oil produced from unroasted seeds), the levels of canolol were 5.8 µg/g (Spielmeyer et al, 2009), 5.19 µg/g (Shrestha andDe Meulenaer, 2014), and 11.54 µg/g (Siger et al, 2015). Kraljić et al (2013) showed that conditioning the seeds prior to pressing the oil had a significant effect on canolol level. They found 3.8-7.8 µg/g canolol in the oil from nonconditioned seeds and 110.3-353.2 µg/g in the oil from conditioned seeds.…”
Section: Changes In Canolol Levelsmentioning
confidence: 99%
“…In analyzing the amounts of particular tocopherol homologues, it was determined that the hot-pressed oil contained 30% more α-T and 16% more γ-T than cold-pressed oil. Kraljić et al (2013) reported that conditioning has a statistically significant effect, increasing the α-T contents of the oil; however, they found no significant effects of conditioning on the level of γ-T. In studies examining the levels of tocopherols in rapeseed oil produced from roasted seeds, some authors observed an increase in the amounts of particular tocopherols and plastochromanol-8 (Siger et al, 2015;Shrestha and De Meulenaer, 2014).…”
Section: Tocochromanol Contentsmentioning
confidence: 99%
See 1 more Smart Citation